The relationship between digital literacy and innovative behavior among Chinese medical students: the chain mediating roles of diversity experience and creative self-efficacy - Juan Wu; Qilin Zhang; Xiaomin Gan; Xuefang Liu; Jiuying Hu; Yalin Wang (BMC Medical Education)
Abstract Background Innovative behavior and digital literacy are two significant concerns in the cultivation of professional and innovative talents within medical higher education. Although studies suggest that information-related skills positively predict college students’ innovative behavior, research on digital literacy remains limited, and the internal mechanisms through which digital literacy influences innovative behavior have not been clearly elucidated, especially among medical students. This study aims to explore the relationship between digital literacy and innovative behavior among Chinese medical students, with diversity experience and creative self-efficacy acting as chain mediators. Methods A cross-sectional study was conducted among a convenience sample of 887 medical students recruited from Anhui Medical University in China, from May 25 to June 16, 2023. The measures included a digital literacy scale, a diversity experience scale, a creative self-efficacy scale, and an innovative behavior scale. SPSS 25.0 and AMOS 24.0 software were used, and the structural equation model was established to statistically analyze the data. Results The mean values for digital literacy, diversity experience, creative self-efficacy, and innovative behavior among Chinese medical students are above 3 but below 4, and have not yet reached the optimal level. Digital literacy and creative self-efficacy positively predicted innovative behavior. The chain mediating model revealed that diversity experience and creative self-efficacy mediated the effect of digital literacy on innovative behavior, with a total mediation effect value of 0.374, accounting for 45.89% of the total effect (0.815). Specifically, the indirect effect comprised two paths. The first path was digital literacy→creative self-efficacy→innovative behavior, with an effect value of 0.173, accounting for 21.23% of the total effect. The second path was digital literacy→diversity experience→creative self-efficacy→innovative behavior, with an effect value of 0.201, accounting for 24.66% of the total effect. Conclusions This study underscores the significant role that digital literacy plays in directly promoting innovative behavior among medical students, as well as through the simple mediating role of creative self-efficacy and the sequential mediating roles of diversity experience and creative self-efficacy. The findings offer valuable insights into multiple interventions or support mechanisms for encouraging innovative behavior among medical students.